Structural Equation Modeling Relationship between Organizational Support with Self-Esteem and Job Satisfaction - hasan shahriyari; aleme keykha; hasan khalili hoseinabadi; ebrahim haddadi (پژوهش در نظام‌های آموزشی, 2020)
The purpose of the present study was to determine the relationship between organizational support, self-esteem and job satisfaction in Zabol University staff. The covariate method was used to determine 3 samples from the Zabul University staff, and 217 individuals were selected using simple random sampling method. Were. Data were collected from standard organizational support programs of Alan et al. (2008), Cooper Smith Self-esteem (1990) and Minnesota Job Satisfaction (2009), which assess the relevance of job placement and validity. Also by using the combined Mr Cronbach's equation 0.96, 0.77 and 0.95 were calculated respectively. For both data, SpSS23 and SmartPLS3 statistical software was developed. There was a significant relationship (P <0.05) between organizational support and employees 'self-esteem and job satisfaction, and job characteristics and organizational activity had a positive and significant relationship and job stress had a negative and significant relationship with employees' self-esteem. And it's their job satisfaction. . .